The Meaning of the Term Fitrah in the Quran: A Concept of Islamic Education - Ruslan Ruslan; Ahmad Syukron Latif (Al-Musannif, 2025)
The concept of Islamic education began to be oriented towards Western theory, and the study of the Quran as a source of Islamic education began to diminish. This research examines (1) the meaning of the term fitrah in the Quran and (2) its implications for the concept of Islamic education. This literature review study uses tafsir maudui (thematic interpretation) and pedagogical approaches in analyzing the data. The data sources consist of Quran, commentary books, and several relevant books and journals. The results of the research show that fitrah in the Quran is the default factory setting for humans. Fitrah is a divine chip implanted by God in humans so that they are ready to believe in monotheism, purify themselves, and worship God. Humans who carry out their fitrah have three characteristics: accepting and practicing Islam, being sincere, and having a strong faith. Actualization of the concept of human fitrah in Islamic education can be carried out by (1) making fitrah a basic human potential that needs to be developed, (2) making education the main path in developing fitrah, (3) creating a conducive educational environment (helping the development of fitrah), and (4) cultivating a work ethic in which there is harmony and balance between the depth of religious appreciation and activities that lead to increased welfare.